THE DETERMINANTS OF CORPORATE BOND RATING IN INDONESIA - Amran, Harisya (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
This research aims to identify the factors affecting obligation rank on manufacturing corporations. The factors investigated in this research include leverage ratio, liquidity ratio, profitability ratio, activity ratio, and maturity. The population in this research is all non-financial corporations registered in Indonesia Stock Exchange, which has been registered for 5 years, and has published obligations. 47 corporations meet those criteria and become the research sample. Data analysis on this research use logistic regression analysis. The result shows that from five variable researched, only one influence the obligation rank, which is profitability ratio. This result contributes to both theory and practitioners. Keywords: bond rating, leverage ratio, liquidity ratio, profitability ratio, activity ratio, and maturity, logistic regression